Circulating Insulin-Like Growth Factor-1 Is Positively Associated with Growth and Cognition in 6- to 9-Year-Old Schoolchildren from Ghana. Issue 6 (25th March 2020) - Grenov, Benedikte; Larnkjær, Anni; Lee, Reginald; Serena, Anja; Mølgaard, Christian; Michaelsen, Kim F; Manary, Mark J
ABSTRACT: Background: Milk intake stimulates linear growth and improves cognition in children from low-income countries. These effects may be mediated through insulin-like growth factor-1 (IGF-1). Objective: The objective was to assess the effect of milk supplement on circulating IGF-1 and to assess IGF-1 as a correlate of growth and cognition in children. Methods: Secondary data on blood spot IGF-1 from a randomized, double-blind, controlled trial in 6–9-y-old children from rural Ghana were analyzed. Intervention groups received porridge with non–energy-balanced supplements: 8.8 g milk protein/d, 100 kcal/d (Milk8); 4.4 g milk and 4.4 g rice protein/d, 100 kcal/d (Milk/rice); 4.4 g milk protein/d, 48 kcal/d (Milk4); or a control (no protein, 10 kcal/d). IGF-1, length, body composition, and Cambridge Neuropsychological Test Automated Battery (CANTAB) were measured at 3.5 or 8.5 mo. Linear regressions were used to assess the effect of milk interventions on IGF-1 and IGF-1 as a correlate of growth and cognition. Results: The increase in IGF-1 was 15.3 (95% CI: 3.3, 27.3) ng/mL higher in children receiving Milk8 compared with the control. The IGF-1 increases in the isonitrogenous, isoenergetic Milk/rice or the Milk4 groups were not different from the control ( P  ≥ 0.49). The increase in IGF-1 was associated with improvements in 4 out of 5 CANTAB domains. The strongest associations included reductions in "mean correct latency" from Pattern Recognition Memory and "pre-extradimensional (pre-ED) shift errors" from Intra/Extradimensional Set Shift ( P  ≤ 0.005). In addition, change in IGF-1 was positively associated with changes in height, weight, and fat-free mass ( P  ≤ 0.001). Conclusions: Intake of skimmed milk powder corresponding to one, but not half a glass of milk on school days stimulates IGF-1 in 6–9-y-old Ghanian children. IGF-1 seems to mediate the effect of milk intake on growth and cognition. The association between IGF-1 and cognition in relation to milk intake is novel and opens possibilities for dietary interventions to improve cognition.